AUKUS and Australia’s Nuclear-Powered Submarine: A Reinforced Strategic Culture - Muhammad Ilham Ramandha Adamy (Universitas Airlangga, 2022)
Australia’s decision to enter the AUKUS has caused some controversies among regional powers, especially noting the heightened Indo-Pacific discourse lately. But AUKUS isn’t a mere alliance against revisionist power, it has much deeper dan greater significance on Australia’s defence policies. This paper argues that AUKUS reflect the dilemmatic sub-strategic cultures within Australia’s defence policy considerations against the changing strategic environment in Indo-Pacific, the self-reliance and strategic dependence. Strategically, AUKUS presented Australia the opportunity to participate and shaping the Indo-Pacific under US-led initiative and act as technology catalysator on defence sector. Operationally, the nuclear-powered procurement under AUKUS will significantly boost Australia’s submarine fleet capability in sea denial and sea control mission as a part of larger coalition. Using strategic culture lens and studying primary and secondary documents in a qualitative work, the analysis of this paper concludes that AUKUS reflected the return and reinforced pattern of strategic dependence within Australia’s defence policy in the age of Indo-Pacific.